François Gros: from antibiotics to messenger RNA - Yaniv, Moshe (Comptes Rendus Biologies, 2023)
François Gros was a prominent French Molecular Biologist who made a major contribution to the discovery of messenger RNA in 1961. He pursued outstanding research on bacterial mRNA and its translation into proteins followed by pioneering work on muscle differentiation. I was lucky to be among his graduate students and owe much of my success in science to him. In this short text I will describe how the initial post-war studies of François guided him to discover the existence of short-lived RNA in bacteria, the messenger RNA containing the information for protein synthesis. I will also recount the influence he had on his students and their carrier in science.